2023
DOI: 10.4103/ijo.ijo_3020_22
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels in dry eye disease

Abstract: Dry eye disease (DED) which affects millions of people worldwide is an ocular surface disease that is strongly associated with pain, discomfort, and visual disturbances. Altered tear film dynamics, hyperosmolarity, ocular surface inflammation, and neurosensory abnormalities are the key contributors to DED pathogenesis. The presence of discordance between signs and symptoms of DED in patients and refractoriness to current therapies in some patients underpin the need for studying additional contributors that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 130 publications
0
14
0
Order By: Relevance
“…The fluid dynamics of the cornea is a key indicator of eye health, and it is disturbed in many cornea-related degenerative vision diseases. Studies have found that fluid dynamics can affect the barrier function of the corneal endothelium, corneal transparency, and the stability of tear film [9,10] . Therefore, understanding the water content and fluid dynamics of the cornea is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The fluid dynamics of the cornea is a key indicator of eye health, and it is disturbed in many cornea-related degenerative vision diseases. Studies have found that fluid dynamics can affect the barrier function of the corneal endothelium, corneal transparency, and the stability of tear film [9,10] . Therefore, understanding the water content and fluid dynamics of the cornea is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…When sensory neurons in the cornea and conjunctiva detect changes in osmolarity, they transmit signals to the lacrimal glands, initiating tear secretion [18]. A large number of experimental and clinical studies have demonstrated that transient receptor potential (TRP) channels are mainly responsible for the neural regulation of tear production [18][19][20][21][22][23][24][25][26][27][28]. TRP channels belong to a heterogeneous superfamily of widely expressed, functionally varied cation channels that display intricate regulation patterns and are sensitive to a variety of stimuli, including THO [23,24].…”
Section: The Impacts Of Dysfunctional Neural Regulation Of Lacrimal G...mentioning
confidence: 99%
“…A large number of experimental and clinical studies have demonstrated that transient receptor potential (TRP) channels are mainly responsible for the neural regulation of tear production [18][19][20][21][22][23][24][25][26][27][28]. TRP channels belong to a heterogeneous superfamily of widely expressed, functionally varied cation channels that display intricate regulation patterns and are sensitive to a variety of stimuli, including THO [23,24]. Among various TRP channels, the transient receptor potential melastatin 8 (TRPM8) and transient receptor potential vanilloid 1 (TRPV1) are dominantly expressed in sensory neurons of the cornea and conjunctiva [22][23][24].…”
Section: The Impacts Of Dysfunctional Neural Regulation Of Lacrimal G...mentioning
confidence: 99%
See 2 more Smart Citations